The Effectiveness of Acupuncture on Myofascial Trigger Points Versus Traditional Chinese Medicine Acupoints for Treating Plantar Fasciitis With Low Back Pain: A Study Protocol for a Randomised Clinical Trial - Huang Z; Liang X; Luo Y; Fang Z; Xu M; Xu Y; Cheng S; Li L (Journal of Pain Research)
Ziling Huang,1 Xin Liang,1 Yuheng Luo,1 Zhou Fang,2 Ming Xu,1 Yinqin Xu,1 Shan Cheng,3 Lihong Li1 1Department of Acupuncture and Moxibustion, The Affiliated Hospital of Guizhou Medical University, Guizhou, People’s Republic of China; 2Department of Orthopedics, The Affiliated Hospital of Guizhou Medical University, Guizhou, People’s Republic of China; 3Ultrasound Center, The Affiliated Hospital of Guizhou Medical University, Guizhou, People’s Republic of ChinaCorrespondence: Lihong Li, Email 1109718711@qq.comBackground: Plantar fasciitis is a common cause of heel pain, often associated with a higher rate of low back pain. This increased disability rate in low back pain may be correlated with reduced foot and ankle function. While both acupuncture and trigger point dry needling have been reported as potentially effective treatments for plantar fasciitis, the quality of evidence is currently low. Acupuncture at trigger points might be a promising treatment for plantar fasciitis, though there is a lack of evidence supporting its effectiveness. This trial aims to compare the effectiveness of acupuncture at trigger points versus Traditional Chinese Medicine (TCM) acupoints in the treatment of participants with plantar fasciitis and low back pain.Methods: The trial will be a single-centre, parallel two-group, randomised controlled trial with 62 participants allocated in a 1:1 ratio to either the trigger point group or the TCM acupoint group. Patients with plantar fasciitis and low back pain will be enrolled in this trial. Eligible participants will receive acupuncture for 30 minutes per session over 8 total sessions, with a 12-week follow-up period. The primary outcome measure will be the change from baseline in the worst first-step pain intensity in the morning after treatment. Secondary outcomes include changes from baseline in foot and low back pain, foot and low back function, plantar fascia thickness, and participants’ self-reported global improvement. Statistical analysis will be conducted using a two-sided test with a significance level of 0.05 and 95% confidence intervals.Clinical Trial Registration: This trial has been registered at the Chinese Clinical Trial Registry. Registration number: ChiCTR2300067552. Registration date: 1 January 2023.Keywords: acupuncture, trigger point, plantar fasciitis, low back pain, randomised clinical trial